Impact of generic ICD programming on clinical outcomes. (19th May 2022) - Khan, P; Jahagirdar, N; Laybourn, M; Harding, I; Cannata, A; Bromage, D; Shabeeh, H; Kabunga, P; Petzer, E; Murgatroyd, F; Scott, P A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Generic ICD programming, where shock-reduction programming is extrapolated from trials of one manufacturer to another, may reduce non-essential ICD therapies beyond that seen in randomised trials. The purpose of this retrospective cohort study was to evaluate the impact of a standardised programming protocol, based on generic programming, across manufacturers. We also evalutated the impact of combining different detection rates and detection times. Methods: We included all new ICDs in a single centre (2009-2019). In 2013 a standardised programming protocol based on generic programming was introduced. Patients were classified into three groups: pre-guideline (PS), post-guideline and guideline compliant (GC) and post-guideline but not guideline compliant (NGC). The end-points were the first occurrence of any device therapy (ATP or shock), ICD shock, syncope and all-cause mortality. Survival analysis was used to evaluate outcomes. A ''programming score'' was composed based on detection rate and time. The relationship between this composite "programming score'' and study end-points was evaluated in multivariable cox proportional hazards models Results: 1003 patients were included (mean follow-up 1519 +/- 1005 days). In primary prevention patients freedom from ICD therapy (91.5% vs. 73.6%, p<0.001) or shock (94.7% vs 84.8%, p=0.02) were significantly higher in GC compared to PS patients, without significant increase in syncope or mortality. In secondary prevention patients freedom from any ICD therapy or any shock were non-significantly higher in GC compared to PS patients. Among primary prevention patients with the highest 'programming score' (longest detection time and highest detection rates), there was a 82% reduction in risk of any ICD therapy (p<0.001) and a 70% reduction in risk of ICD shock (p<0.001) Conclusion: A standardised programming protocol, incorporating generic programming, reduced the burden of ICD therapy without an increase in adverse outcomes.